Prevalence of Methicillin Resistant Staphylococcus aureus (MRSA) Infection Among Patients in Surgical ad Orthopaedic Wards of PPUKM - Mohamad Noor, Nurul Nadiah; Baba, Mohd Shukri; Mohamad Zin, Noraziah; Hanafiah, Alfizah (2015)
Highly adaptable methicillin-resistant Staphylococcus aureus (MRSA) was documented as the most common commensal pathogen detected in hospitals. Thus, screening for the infection has become one of the essential active control approaches in eradicating the transmission of MRSA which is currently the concern of most medical practitioners. The objective of this study is to compare the prevalence of MRSA infection by universal screening among the patients in surgical and orthopaedic wards of Universiti Kebangsaan Malaysia Medical Center (PPUKM). A total of 41 samples of nasal, throat and armpit swabs were collected from 15 patients in both wards (9 and 6 patients from orthopaedic and surgical ward respectively) and tested on ORSAB media and MSAO agar, before further tested on MHA, DNAse and koagulase media for sensitivity and resistance tests. There were 0% prevalence of MRSA infections recorded out of 25 samples taken from the patients in orthopedic ward, whilst one patient from the surgical ward was positive with MRSA infections (6.25% prevalence) which was obtained from a nasal sample. The result show that the prevalence of MRSA infection in surgical ward was potentially higher as compared to orthopaedic ward although there were smaller number of samples taken from the surgical ward. There is also a tendency that MRSA inhabiting nasal in a relatively higher number than in throat or armpit surfaces of warded patients.